Investigation of Mechanical and Physical Properties of Eggshell Reinforced with Different Type of Resin - Mohamad, Zaleha; Roslan, Muhammad Hakim (Research Progress in Mechanical and Manufacturing Engineering, 2020)
The eggshell that came from the food industries is considered as the non-hazardous waste but can cause environmental pollution. Considering the eggshell waste are rich in calcium carbonate (CaCO3), it is possible to be used as the sustainability insulation product to help the bio-economy society and replace the uses of hazardous asbestos insulation. In this review, the tensile strength, sound absorption, and thermal conductivity properties of the eggshell waste composite were discussed. The eggshell powder was characterized under the XRD test. The different types of resins with varied compositions reinforced with the eggshell powder. The result from the XRD pattern of ESP shows the mostly the peak of the pattern was CaCO3. For the tensile test, the tensile strength increasing when the composition increase. The higher composition of the filler content gives the optimum the sound absorption coefficient but in a specific range of the frequency. The thermal conductivity, decreasing when added more percentage of ESP content but certain results show increasing due to different parameter uses. The comparison between asbestos properties, the eggshell composite has potential as the insulation material